Challenges and supports for educator well-being: perspectives of Australian early childhood educators during the COVID-19 pandemic. (4th July 2022) - Eadie, Patricia; Murray, Lisa; Levickis, Penny; Page, Jane; Church, Amelia; Elek, Catriona
ABSTRACT: The COVID-19 pandemic highlighted the importance of early childhood education and care (ECEC) as an essential service for families and the economy. However, it also exacerbated persisting challenges for the sector which impact educator well-being. This paper reports findings from a qualitative study that investigated Australian early childhood educators' perspectives about the impact of the COVID-19 pandemic, and challenges and supports for educator well-being. A sample of 214 ECEC professionals responded to an online survey and 15 educators participated in subsequent focus groups. Five themes were identified in the data from open-ended survey questions and the focus groups: (1) threats to physical, emotional and financial health; (2) self-care and access to well-being resources; (3) connection with children and families; (4) a supportive professional community; and (5) acknowledging the value of early childhood education. These themes are elucidated using the 'voices' of educators, providing insights into how educator well-being can be supported during and beyond the pandemic.